Water-centered ecotourism planning: ecohydrological capacity and institutional barriers in a semiarid metropolis - Kooshki, Parisa; Esmaeilzadeh, Hassan; Barghjelveh, Shahindokht; Deljouei, Azade; Marcu, Marina Viorela; Sadeghi, Seyed Mohammad Moein (Frontiers in Water, 2026)
Balancing ecotourism development with water resource sustainability is an urgent challenge for semiarid cities experiencing escalating water stress. Tehran, a rapidly expanding Middle Eastern metropolis, has faced acute water scarcity in recent years, making water-entered planning critical for sustainable tourism. This study combines ecological capability evaluation (ECE), GIS-based multi-criteria analysis, and institutional review to delineate suitable zones for ecotourism. Twenty-three indicators across physical, ecohydrological, and socio-economic dimensions were weighted using the Analytic Hierarchy Process (AHP) and integrated through Weighted Linear Combination (WLC). Results showed a clear spatial polarization: northern highlands and river valleys, with higher precipitation and abundant surface water, were identified as the most suitable areas for both intensive and extensive ecotourism, while southern plains with chronic water scarcity and flood risk were classified as unsuitable. More than 60% of intensive ecotourism zones are located within 1 km of perennial rivers, underscoring the decisive role of surface water. Extensive ecotourism suitability was more strongly associated with upland regions combining groundwater accessibility and higher rainfall. This study shows that water is not merely a limiting resource but the strategic axis around which ecotourism planning in semiarid cities must be organized. The framework developed here provides a decision-support tool for Tehran and offers transferable guidance for semiarid metropolitan regions confronting water scarcity and uncoordinated land-use expansion.